SOCIAL STRUCTURAL CHARACTERISTICS OF PSYCHOLOGICAL EMPOWERMENT. - Spreitzer, G. M. (Academy of Management Journal, 1996)
A set of hypotheses based on emerging theory on high-involvement systems describes expected relationships between social structural characteristics at the level of the work unit (perceptions of role ambiguity, span of control, sociopolitical support, access to information and resources, and work unit climate) and feelings of empowerment. The hypotheses are examined with data on a sample of middle managers from diverse units of a Fortune 50 organization. A work unit with little role ambiguity, strong sociopolitical support, access to information, and a participative unit climate is found to be associated with managerial perceptions of empowerment, as is working for a boss who has a wide span of control.